Dealing with reducing trends in forest ecosystem services through a vulnerability assessment and planned adaptation actions - Idinoba, M.; Nkem, J.; Kalame, F.B.; Tachie-Obeng, E.; Gyampoh, B.A. (2010)
Vulnerability of forest ecosystems in West Africa is likely to be aggravated with current and projected climate and human stresses with implications for adaptation and REDD regimes. This is because vulnerability of the forest ecosystems affects economic sectors and millions of people that depend on their services. This study investigated vulnerability of forest ecosystems through land use land cover (LULC) changes and the availability of economically useful forest ecosystem provisioning services in Ghana and Burkina Faso in the face of different stresses using landsat imageries and Participatory Rural Appraisal. Our analysis indicates that current and projected land cover changes and local perception on availability of forest resources in the different ecological zones are facing a decreasing trend due to various climatic and anthropogenic drivers. Ghana shows a transition in the order of high forest, forest-savanna transition, savanna to widely open cultivated savanna, while study areas in Burkina Faso is experiencing a gradual reduction of dense natural forests reserves towards a more sparse vegetation. Local knowledge in addition to observed changes in LULC can be a useful resource in preparing communities and ecosystems for adaptation as well as contribute to the input based adoption of appropriate policies in REDD schemes.